Penerapan Model Pembelajaran Numbered Heads Together Untuk Meningkatkan Hasil Belajar Ipa Siswa Kelas V Sd Gmim Iv Tomohon - Komedien, Brianne E.Jo.; Rawis, Joulanda A.M.; Manoppo, Jenelyn Devinda (Peneliti.net, 2023)
The aim of this research is to improve science learning outcomes by implementing the Numbered Heads Together learning model for class V students at SD GMIM IV Tomohon. Researchers used a Classroom Action Research (PTK) design, according to Kemmis and Mc. Taggart (Zinal Aqib, 2006:31) which includes four stages, namely: (1) planning, (2) action, (3) observation, and (4) reflection which is carried out in two cycles. The subjects of this research were class V students at SD GMIM IV Tomohon using the Numbered Heads Together learning model. The data collection technique was carried out through observation, namely by directly observing the implementation of learning actions and written tests to determine the extent to which students were able to understand the material from the two cycles. The data analysis technique uses the formula KB = T/Tt x 100%. The results obtained in cycle I reached 63.66%, while in cycle II student learning outcomes reached 85%. Students understood and were able to achieve the learning objectives and expected learning outcomes. Based on the results of the research and discussion, it can be concluded that applying the Numbered Heads Together learning model can improve the science learning outcomes of class V students at SD GMIM IV Tomohon.